The Socioeconomic Impacts of the Jabodetabek Economic-Class Electric Rail Train during 1976-2013 - Fauzan Syahru Ramadhan; Desi Susanti; Khairana Zata Nugroho; Bryna Rizkinta Sembiring Meliala (Mahesa Research Center (PT. Mahesa Global Publishing), 2025)
This article examines the socio-economic impacts of the Jabodetabek Economic Electric Rail Train operation towards the surrounding community from 1976 to 2013. The study analyzes the development of the transportation and the response of community. The research highlights how the existence of the transportation caused various significant impacts both positively and negatively. The present study employs a historical method incorporating heuristics, criticism, interpretation, and historiography to analyze the phenomenon. The findings reveal that, while the presence of the Electric Rail Train yielded positive socio-economic impacts, such as fostering potential cooperation and generating employment opportunities within the community, it also concomitantly led to an escalation in crime and conflict, including thuggery, pickpocketing, and vandalism, within the train-crossing areas. The article concludes that the train’s operation had engendered a dilemma, stemming from the high intensity of social interaction characterizing the station and its evolution into a commercial hub for the local community.